Multidimensional fractionation of complex polymers by comprehensive online-coupled thermal field-flow fractionation and size exclusion chromatography. - Viktor, Zanelle (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.